ESTIMATION OF CARBON RESERVES IN SEDIMENTS IN THE MANGROVE ECOSYSTEM OF BUKIT BATU VILLAGE, BENGKALIS REGENCY, RIAU - Dermawan, Ernanda Putra; Siregar, , Yusni Ikhwan; Efriyeldi, Efriyeldi (Asian Journal of Aquatic Sciences, 2023)
This research was carried out in December 2021. Sampling and water quality measurements were carried out in the Bukit Batu Muara River, Bengkalis Regency, Riau Province. Sample analysis was continued at the Marine Chemistry Laboratory, Department of Marine Science, Faculty of Fisheries and Marine, Universitas Riau. The purpose of this study was to determine the estimation of carbon stocks in sediments, the comparison of carbon stocks between transects, and the relationship between density and carbon stocks in the Muara Sungai Bukit Batu mangrove area, Bengkalis Regency, Riau Province. The method used in this study is a survey method. Parameters measured included mangrove density (Ind/Ha), organic matter content, and carbon stock in sediments. In addition, water quality was also measured in the form of temperature, salinity, and degree of acidity. Analysis of carbon stock using the loss on ignition method. The result of average density of mangroves throughout the transect is 3733.33 (Ind/Ha). The lowest carbon stock value in sediments is in transect 2 with medium mangrove density with a value of 29.26 tons/ha, while the highest carbon stock value is in transect 3 with high-density mangrove areas with a value of 36.15 tons/ha. The results of a simple linear regression to determine the relationship between mangrove density and carbon stock show a coefficient of determination R² = 0.023, which means that 2.3% of total carbon stock is affected by density, while 97.7% is influenced by other factors. The value of R = 0.152, which means that the relationship between density and carbon stock in the Bukit Batu river estuary area, Bengkalis Regency, is low.